Optimization of Voltammetric Determination of Dysprosium (III) Using Plackett-Burman and RSM-CCD Experimental Designs (Baghdad Science Journal, 2020)
This study was aimed to develop an optimized Dy determination method using differential pulse voltammetry (DPV). The Plackett-Burman (PB) experimental design was used to select significant factors that affect the electrical current response, which were further optimized using the response surface method-central composite design (RSM-CCD). The type of electrolyte solution and amplitude modulation were found as two most significant factors, among the nine factors tested, which enhance the current response based on PB design. Further optimization using RSM-CCD shows that the optimum values for the two factors were 0.1046 M and 0.1082 V respectively. When the optimum conditions were applied for Dy determination good recovery and precision were achieved with values of 91.58%, and 99.80%, respectively. The detection limit and quantification limit of the method were 1.4322 mg/L and of 4.7741 mg/L, respectively.